Swarm Intelligence 9th International Conference, ANTS 2014, Brussels, Belgium, September 10-12, 2014. Proceedings - Dorigo, Marco; Birattari, Mauro; Garnier, Simon; Hamann, Heiko; Montes de Oca, Marco; Solnon, Christine; Stützle, Thomas (Theoretical Computer Science and General Issues, 2014)
This book constitutes the proceedings of the 9th International Conference on Swarm Intelligence, held in Brussels, Belgium, in September 2014. This volume contains 17 full papers, 9 short papers, and 7 extended abstracts carefully selected out of 55 submissions. The papers cover empirical and theoretical research in swarm intelligence such as: behavioral models of social insects or other animal societies, ant colony optimization, particle swarm optimization, swarm robotics systems.